Detailed numerical simulation of swirling primary atomization using a mass conservative level set method. (March 2017) - Shao, Changxiao; Luo, Kun; Yang, Yue; Fan, Jianren
Highlights: We report detailed numerical simulations of swirling liquid atomization by using a recently developed mass conservative level set method. Through comparing the sheet thickness, the breakup length and the cone angle, the numerical convergence of the global characteristics of the swirling two phase flow has been obtained. The numerical results show that turbulent inflow can induce liquid sheet breakup near the nozzle exit, reduce the stiffness of the liquid sheet, and lead to the statistically homogeneous distribution of small-scale liquid structures in the radial direction. Compared with the single-phase jet, the two-phase jet exhibits the chaotic velocity filed downstream that can enhance the mixing of droplets and ambient gas, and the precessing vortex core (PVC) is not observed in the center of the two-phase jet. The preferential alignment of ω i with the intermediate strain rate indicates that the fluctuating velocity in the recirculation zone is statistically similar to isotropic turbulence. Abstract: We report detailed numerical simulations of swirling liquid atomization. A recently developed mass conservative level set method is employed to capture the gas–liquid interface and a ghost fluid method is utilized to deal with the jump conditions across the interface. The swirl and atomization characteristics of two-phase annular swirling jets with the influence of turbulent inflow are investigated. Through comparing the sheet thickness, the breakup length and the cone angle, the numerical convergence of the global characteristics of the swirling two phase flow has been obtained. The numerical results show that turbulent inflow can induce liquid sheet breakup near the nozzle exit, reduce the stiffness of the liquid sheet, and lead to the statistically homogeneous distribution of small-scale liquid structures in the radial direction. Compared with the single-phase jet, the two-phase jet exhibits the chaotic velocity filed downstream that can enhance the mixing of droplets and ambient gas, and the precessing vortex core (PVC) is not observed in the center of the two-phase jet. In addition, the recirculation zone is smaller and farther from the nozzle exit for the turbulent inflow case than that from the laminar inflow case, and the preferential alignment of ω i with the intermediate strain rate indicates that the fluctuating velocity in the recirculation zone is statistically similar to isotropic turbulence. The interaction of the liquid-gas interface and vortices shows the preferential normal alignment of the vorticity and the normal of the interface, and the liquid sheet can generate high shear layers to produce anisotropic small-scale fluctuations.